Digital and postdigital art: from aesthetics of a subject to the ontology of an object - Khandogin, Ruslan (GeSec : Revista de Gestão e Secretariado, 2023)
The study highlights the increasing diversity of digital and postdigital art along with its rising or even defining influence on various phenomena and spheres of sociocultural reality. Based on ideological attitudes and value orientations, the media reality, through the ontologization of digital and postdigital art, becomes a social model of understanding reality and social life, while organizing communication, interpretation of meanings, and translation of ideas in a special way. In counterpoint to the scientific, technocratic paradigm, which in many respects dominates the digital and postdigital realm, the digital and postdigital space simultaneously becomes an arena for the revival of archaic consciousness. The essential and content foundations and aspects of the digital and postdigital manifest the categorical, conceptual, and essential ideas of art in general. They interact with the social, cultural, political, as well as geographical and topological, environments to the point of creating new cultural, social, symbolic, and material phenomena, hybrid and transformed forms. The essence of beauty is accessed through representations, mediated by symbolic, semantic, and essential agents. The study addresses specific aspects of digital art from the standpoint of materialistic approaches, postmodern concepts, network theories, and social constructivism. Particular attention is paid to the ontologization of art objects in the framework of object-oriented philosophy. Art objects acquire their ontological status from their own authenticity and gain their reality from the outside. Digital and postdigital art combines the immanent with the transcendent, which makes its objects possible or necessary, perceivable or real. Digital and postdigital art is marked by duality and ambivalence, which form a holistic unity in the aspects of object-subject relations and the social and non-human sections of reality.